From geographical innovation clusters towards virtual innovation clusters: The innovation virtual system - Giuseppina Passiante; Giustina Secundo (European Regional Science Association (ERSA), 2002)
The opportunities of the new economic landscape have determined radical changes in the organizational structures of the firms, till the creation of new virtual clusterization forms, that is distinct systems of suppliers, distributors, service providers and clients that use the 'internetworking technologies' as a principal way for co-operating and competing. These 'virtual clusterization forms' that have been also defined as 'e-business communities' or 'b-web communities' (Tapscott, Lowy & Ticoll, 2000), are here defined as 'virtual clusters'. In a virtual cluster (VC), each enterprise adds one or more distinct aspects of product/service value to the value of the network, by exchanging digital knowledge with other members. Recent studies, focused on VCs, highlight that the VC enabling factors may be identified in ICTs ubiquity (increasingly wireless) and bandwidth robustness, that allow firms to access real-time what they need and to co-ordinate their intra and inter-firm activities, creating value both by offering innovative and personalized products, services and by cutting transaction costs. (Davin and Botkin, 1994) (Rayport and Sviokla, 1995). This paper focuses on these VCs innovation processes, in order to make some comparisons between the traditional geographical innovation clusters and the emerging virtual innovation clusters. To this end, the paper is organized in two logical patterns: Some empirical evidence for describing ad discussing the more important features of the emerging VCs. Specifically, the paper focuses on the following issues: - Some first results on VCs characteristics, regarding four distinctive features of their new world of business: i. Agents: radical increase in the number of agents that form a cluster. ii. Connections: virtually unlimited increase in the number of connections and therefore in the potential size of the cluster. iii. Space: delocalization of transactions which become space independent. iv. Time: information transmission takes place at the speed of electronic communication. - The analysis of the VC basic unit, the Internetworked Enterprise (IE), and of its learning process with customers and trough strategic alliances. A model of the VCs global virtual learning environment, here conceived as a system of innovation, defined as 'Innovation Virtual System' (IVS). IVS is here interpreted as a new way of projecting the traditional systems of innovation into a global scale.
Keywords: 330